Risk factors for bloodstream infections due to extended-spectrum β-lactamase producing Enterobacteriaceae in cancer patients - Sabahat Ceken; Gulsen Iskender; Habip Gedik; Fazilet Duygu; Duygu Mert; Ali Hakan Kaya; Fevzi Altuntas; Mustafa Ertek (Journal of Infection in Developing Countries)
Introduction: Bloodstream infection (BSI) caused by Enterobacteriaceae is associated with mortality in cancer patients receiving chemotherapy. The aim of this study is to identify the risk factors and outcomes related to BSIs caused by extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae in cancer patients.